Phenotype Difference between Familial and Sporadic Ankylosing Spondylitis in Korean Patients - Kim, Hye Won (The Korean Academy of Medical Sciences, 2014)
Clustered occurrences of ankylosing spondylitis (AS) in family have been noticed. We evaluated patients with AS confirmed by the modified New York criteria for familial history of AS (one or more first to third degree relatives). The clinical characteristics and the recurrence risks (number of AS patients/number of familial members) of the familial AS compared to sporadic AS were investigated. Out of a total of 204 AS patients, 38 patients (18.6%) reported that they had a familial history of AS. The recurrence risks in the familial AS patients for first, second and third degree family members were 14.5%, 5.2%, and 4.4% respectively. Erythrocyte sedimentation rate (ESR) (22.6±22.2 vs 35.4±34.4, P=0.029) and C-reactive protein (CRP) (1.24±1.7 vs 2.43±3.3, P=0.003) at diagnosis, body mass index (21.9±2.7 vs 23.7±3.3, P=0.002) and frequency of oligoarthritis (13.2% vs 33.7%, P=0.021) were significantly lower in the familial form. The presence of HLA-B27 (97.4% vs 83.1%, P=0.044) was significantly higher in familial AS. In conclusion, Korean familial AS patients show a lower frequency of oligoarthritis, lower BMI, lower ESR and CRP at diagnosis and higher presence of HLA-B27. GRAPHICAL ABSTRACT: [Image: see text]